The interrelation scheme of access networks parameters - Sakharova, Svetlana; Konyshev, Eugene (Видавництво Львівської політехніки, 2012)
Work is devoted the decision of access networks parameters problem analysis and correlation revealing between them. The example of an establishment of relations between components of cost of access networks is presented.
Keywords: Access network; parameters of access networks; correlation between parameters; the interrelation scheme